PERSPECTIVES, POINTS OF VIEW, AND FRAMES. ON THE POSSIBILITY OF EVALUATING POINTS OF VIEW PERSPECTIVES, POINTS OF VIEW, AND FRAMES. ON THE POSSIBILITY OF EVALUATING POINTS OF VIEW - Jaume, Andrés (Analysis. Journal of Philosophical Research, 2024)
This collaboration addresses the difference between the concepts of perspective, point of view, and conceptual framework. This distinction allows us to avoid the problem of circularity in philosophical perspectivism while preventing us from falling into relativism. The basic notion is perspective, and points of view are understood as ways of conceptualizing certain aspects of reality. Conceptual frameworks are seen as systems of points of view that can have a greater or lesser scope. Finally, the concept of personal fulfillment is proposed as the ultimate criterion for determining how it is possible to improve one's point of view, since it is assumed that not all points of view have the same value, against skeptical assumptions, and that consequently, there is no room for vicious circularity in the philosophical perspectivism upheld here.